Substance P in the lateral hypothalamic area regulates binge‐like eating behaviors in mice - Xin-Yue Lv; Qian-Qian Yang; Yue Wang; Si-Ran Wang; Jiu-Ye Qiao; Shuang Liu; Hua-Li Yu; Xiao-Xiao He; Xiao-Juan Zhu; Zi-Xuan He (Proceedings of the National Academy of Sciences, 2026)
Binge eating disorder (BED) is the most common type of eating disorder; however, the neural circuit mechanisms underlying BED remain elusive. Here, we report that tachykinin-expressing neurons in the lateral hypothalamic area (LH Tac1 neurons) are inhibited during binge-like eating behaviors in mice. We identified LH Tac1 neurons as key mediators of binge-like eating behaviors and reported that the LH Tac1 → lateral periaqueductal gray (LPAG) circuit is critical to the regulation of binge-like eating behaviors. Moreover, Substance P (SP) released by LH Tac1 neurons modulates binge-like eating behaviors by influencing the input of glutamate to LPAG cells, which receive projections from LH Tac1 neurons. In summary, these findings point to the SP as a key node in BED circuits.